An optimized live bacterial delivery vehicle safely and efficaciously delivers bacterially transcribed therapeutic nucleic acids. Issue 3 (5th February 2023) - Mora, Darcy S. O.; Cox, Madeline; Magunda, Forgivemore; Williams, Ashley B.; Linke, Lyndsey
Abstract: There is an unmet need for delivery platforms that realize the full potential of next‐generation nucleic acid therapeutics. The in vivo usefulness of current delivery systems is limited by numerous weaknesses, including poor targeting specificity, inefficient access to target cell cytoplasm, immune activation, off‐target effects, small therapeutic windows, limited genetic encoding and cargo capacity, and manufacturing challenges. Here we characterize the safety and efficacy of a delivery platform comprising engineered live, tissue‐targeting, non‐pathogenic bacteria ( Escherichia coli SVC1) for intracellular cargo delivery. SVC1 bacteria are engineered to specifically bind to epithelial cells via a surface‐expressed targeting ligand, to allow escape of their cargo from the phagosome, and to have minimal immunogenicity. We describe SVC1's ability to deliver short hairpin RNA (shRNA), localized SVC1 administration to various tissues, and its minimal immunogenicity. To validate the therapeutic potential of SVC1, we used it to deliver influenza‐targeting antiviral shRNAs to respiratory tissues in vivo. These data are the first to establish the safety and efficacy of this bacteria‐based delivery platform for use in multiple tissue types and as an antiviral in the mammalian respiratory tract. We expect that this optimized delivery platform will enable a variety of advanced therapeutic approaches.